Associations between objectively and subjectively measured sleep outcomes among elementary school children in Rhode Island - Rodriguez Acevedo, Aliana; Story, Diane; Werner, Lovisa; Barker, David H.; McGeary, John E.; Dunsiger, Shira I.; Grigsby-Toussaint, Diana S. (Frontiers in Pediatrics, 2025)
ObjectiveAlthough sleep is essential for healthy child development, parents generally misconstrue definitions of sleep duration and sleep quality. This study examines differences between objective and parent-reported measures of sleep in children, with a particular focus on Latino and non-Latino groups. We hypothesized that significant discrepancies exist between objective and subjective sleep measures and differences in sleep outcomes between Latino and non-Latino subgroups.MethodsChildren in grades one, two, and three in Rhode Island (n = 102; age range 6–10 years; 57.8% female) wore an accelerometer for seven days to objectively measure time in bed, sleep duration, wake after sleep onset, and sleep latency. Parents also reported perceived sleep outcomes, and whether they believed their child generally “sleeps the right amount”. Emphasis was placed on the Latino population.ResultsBased on parent-reported sleep measures, 83.3% of children met sleep guidelines (defined as 9–12 h per night), compared to 14.7% based on accelerometry (ρ = −0.036, p = 0.711). Average sleep duration significantly differed between parent reports (9.58 h, SD = 1.42) and actigraphy (8.32 h, SD = 0.70; ρ = 0.405, p < 0.001). There were no discrepancies between objective and subjective reported sleep latency and WASO, although paired tests indicated significant within-person differences in WASO (p < .001). Finally, there were significant discrepancies in sleep duration between Latinos and non-Latinos, with Latino caregivers reporting significantly shorter sleep and their children experiencing shorter sleep duration as measured via actigraphy, and being less likely to meet sleep guidelines.ConclusionThese findings suggest that there is a discrepancy between perceived and objectively measured sleep. It also suggests discrepancies in sleep duration between Latino and non-Latino children, and differences in parental knowledge of sleep behaviors between Latinos and non-Latinos.